The economic crisis of 2008 through four film documentaries: Testimony, debate and reflection - Redondo Neira, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The purpose of this article is to study how the documentary represented the deep economic crisis that began in 2008 in Spain. We propose to apply a methodology of filmic analysis that let us generate a new knowledge about this issue. We will study Edificio España (Víctor Moreno, 2012), Libre te quiero (Basilio Martín Patino, 2012), VidaExtra (Ramiro Ledo Cordeiro, 2013) and Informe General II (Pere Portabella, 2015). Between the first film and the last one there is the following evolution: antecedents, the testimony of the protest, the debate on the immediate events and the analysis elaborated from a larger reflective distance.